RANCANG BANGUN SISTEM INFORMASI PENJUALAN ONLINE BERBASIS WEB MOBILE DENGAN PENDEKATAN WATERFALL - Migunani Migunani; Arditya Himawan (UNIVERSITAS STEKOM, 2021)
PT XYZ is a computer shop engaged in the sale of laptops, computers, spare parts, accessories supporting and providing repair services. The marketing process is less than optimal because it only sells by phone or social media. There are some problems that occur between them : (1) Stock management is not optimal because of frequent discrepancies between stock records with the amount of goods available so often consumers feel disappointed with the services provided, (2) The issue of uploaded ad duration in uploaded social media will alternate from one product content display to another in a relatively short period of time, (3) The absence of management of consumer sales transactions thus requiring recording of repeated transactions, (4) The decline in sales turnover in recent months (5). The management of customer or consumer data is less noticed. Based on these problems, this study aims to design a web-based online sales information system mobile on PT XYZ . This research uses the development of SDLC waterfall model system which consists of planning, analysis, design, implementation and maintenance. Using PHP and MySQL Server programming language as database. The results of research in the form of Online Sales Information System Web-Based Mobile that can facilitate consumers to view products, make reservations for consumers and management for the admin. This information system is equipped with product management features, order data management, customer data management, preparing order reports and payment confirmation. So that this information system can provide convenience both consumer and admin on PT XYZ